An Assay to Determine Phagocytosis of Apoptotic Cells by Cardiac Macrophages and Cardiac Myofibroblasts - Yuma Horii; Shoichi Matsuda; Kenji Watari; Akiomi Nagasaka; Hitoshi Kurose; Michio Nakaya (Bio-Protocol, 2017)
In myocardial infarction (MI), a number of cardiomyocytes undergo apoptosis. These apoptotic cardiomyocytes are promptly engulfed by phagocytes. If the dead cells are not engulfed, their noxious contents are released outside, resulting in induction of inflammation. Therefore, the removal of these dead cells is necessary. However, the contribution of each phagocyte type to the removal of apoptotic cells in infarcted hearts remains unresolved. Here, we describe an in vitro protocol for a phagocytosis assay to compare the engulfment ability of cardiac macrophages and cardiac myofibroblasts.